2019
DOI: 10.3389/fpls.2019.00826
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in Sexual Dimorphism Enhances Adaptation of Dioecious Vallisneria natans Plants to Water Depth Change

Abstract: Sexual dimorphism in vegetative and reproductive traits is associated with contrasting strategies of males and females for response to varied environmental conditions, causing sex-specific reproduction success and consequently long-distance dispersal and colonization. Aquatic plants usually exhibit rich phenotypic plasticity and great diversity in reproductive systems, but the influence of aquatic conditions on the plasticity of sexual dimorphism has received less attention. Using a common garden experiment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Sexual dimorphism in vegetative and reproductive traits is also associated with varying strategies of male and female functions in response to the environment and helps a species to adapt in varying environmental conditions (e.g., Vallisneria sp., Mercurialis annua , Salix sp . [ 44 46 ]. In the present study, out of the three natural populations investigated, overall, only the SK population (male-biased population) exhibited a limited extent of variability than the other two populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphism in vegetative and reproductive traits is also associated with varying strategies of male and female functions in response to the environment and helps a species to adapt in varying environmental conditions (e.g., Vallisneria sp., Mercurialis annua , Salix sp . [ 44 46 ]. In the present study, out of the three natural populations investigated, overall, only the SK population (male-biased population) exhibited a limited extent of variability than the other two populations.…”
Section: Discussionmentioning
confidence: 99%
“…At SK, females had lowest reproductive output (lowest fruit-set), and higher proportion of thorns than CV and SD. The magnitude of differences in the other traits (except fruit set and thorns) of the species did not show significant difference among the populations, thereby ruling out the incidence of phenotypic plasticity [ 43 , 46 48 ]. The PCA analysis indicates that sex-based differences between male and female traits are, overlapped (i.e., Height, Circumference, FWL, DWL, and SLA) with PGM plants ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, males are generally more brightly colored, but they can also exhibit darker flower colors. Recently, this plasticity in dimorphism was reported to be adaptive in dioecious aquatic plants that were treated to varying environmental conditions (Zhou et al 2019). More studies are needed on terrestrial plants to ascertain if this strategy prevails across dioecious plants.…”
Section: Discussionmentioning
confidence: 99%
“…(Greco et al 2013). Previous studies on the response of V. natans to changes in different water depths have shown that female individuals showed greater investment in leaf length and biomass than male ones and that females were more plastic to environmental stress (Zhou et al 2019). In our experiments, female individuals had higher biomass than male ones, but there was no difference in leaf length between females and males probably due to the size limitation of our experimental microcosm.…”
Section: Growth Traits Of Mature Individuals By the End Of Phase Imentioning
confidence: 98%